PENGARUH KOLOM PASIR TERHADAP KONSOLIDASI TANAH LEMPUNG LUNAK - Anto Budi Listyawan; Qunik Wiqoyah; Rena Ningsih; Marten Widhi Satriyana Ramadlan Widhi Satriyana (Eco Rekayasa: Jurnal Teknik Sipil, 2015)
The  road weaving near Sragen city Central Java has been daily problem  in  last decade. The  existing of high expansive  clay soil in subgrade below the road foundation has been identified as the major cause of this problem. Sand Column become one solution to improve the subgrade since it can ab-sorb the water  from the void of clay soil and drain into the channel. The re-search develops a model of Sand column in laboratorium. The box of 1.0 m x 0.4 m x 0.4 m has been created. 15 cm diameter of sand column then installed at the toe and samples for consolidation test are taken from various distances from the centre of column (i.e. 16.67 cm; 33.33 cm; and 50 cm). The result shows that the Sand Column can improve the soft clay soil in terms of consolidation. The coefficient of consolidation increases as the compression index drops. Consequently, the consolidation settlement can be re-duced significantly.